Leadership Style and Work Environment on Employee Performance - Cahyani, Fitiara Adistha; Diana, Diana; Jamiah, Jamiah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The background of the problem in this study is that there are many problems encountered in the company PT. Kharisma Anugrah Lestari is that there are still many employees who do not comply with work regulations at the company, employees also show lack of work performance, lack of responsibility for work, the need for efforts made by PT. Kharisma Anugrah Lestari to improve effective employee performance. These problems raise the need for a leadership style in managing human resources in a work unit and a supportive work environment. So, the author is interested in conducting further research entitled